KONTRIBUSI TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP PENINGKATAN NILAI TAMBAH SEKTOR PARIWISATA DI JAWA TENGAH - Ika Yuni Wulansari; Dyah Makutaning Dewi (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2020)
Indonesia is one of the countries with rapid development of information and communication technology (ICT). The rapid development of ICT can encourage tourism sector, one of them in the province of Central Java. However, there are several districts or cities that experienced negative relation between internet users rate and value added of tourism sector. This research aims to provide an overview of the conditions of tourism sector and the percentage of internet users in Central Java and know the influence of ICT on increasing the value added of tourism sector in Central Java in 2015-2018. This research used panel data from Statistics Indonesia and Department of Youth, Sports and Tourism Central Java. The results showes that the percentage of internet users, the number of workers in tourism business, and capital expenditure have positive and significant impact to the value added of tourism sector in Central Java. Therefore, increase the value added of tourism sector need to be supported by increased promotion via Internet. In addition, the Government's role is required in allocating capital for tourism sector development.